2022
DOI: 10.3389/fimmu.2022.868813
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Breast Cancer Microenvironment Through Single-Cell Omics

Abstract: Breast cancer development and progression rely not only on the proliferation of neoplastic cells but also on the significant heterogeneity in the surrounding tumor microenvironment. Its unique microenvironment, including tumor-infiltrating lymphocytes, complex myeloid cells, lipid-associated macrophages, cancer-associated fibroblasts (CAFs), and other molecules that promote the growth and migration of tumor cells, has been shown to play a crucial role in the occurrence, growth, and metastasis of breast cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 86 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Breast cancer development and progression are enabled and mediated not only by the proliferation of neoplastic cells, but also by numerous interactions with heterogeneous segments that create the surrounding tumor microenvironment. Such important factors are tumor-infiltrating lymphocytes, complex myeloid cells, lipid-associated macrophages, cancer-associated fibroblasts ( CAFs ), and other molecules that promote the growth and migration of tumor cells [ 99 ]. Tumor-infiltrating lymphocytes ( TIL ) are considered an important prognostic factor in various types of oncological diseases [ 100 , 101 , 102 , 103 , 104 ] including triple-negative breast cancer ( TNBC ) [ 105 , 106 ].…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
“…Breast cancer development and progression are enabled and mediated not only by the proliferation of neoplastic cells, but also by numerous interactions with heterogeneous segments that create the surrounding tumor microenvironment. Such important factors are tumor-infiltrating lymphocytes, complex myeloid cells, lipid-associated macrophages, cancer-associated fibroblasts ( CAFs ), and other molecules that promote the growth and migration of tumor cells [ 99 ]. Tumor-infiltrating lymphocytes ( TIL ) are considered an important prognostic factor in various types of oncological diseases [ 100 , 101 , 102 , 103 , 104 ] including triple-negative breast cancer ( TNBC ) [ 105 , 106 ].…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
“…These pathways have been implicated in several types of cancer and suggest that the differentially expressed genes identi ed in our study may play critical roles in regulating BC pathogenesis [29][30][31]. The nding that broblast, cancer cell, and cycling cell types have relatively high expression of NAC-related genes is particularly relevant as these cells are known to play important roles in BC pathogenesis [32][33][34][35].…”
Section: Discussionmentioning
confidence: 59%
“…These TAM also express programmed-death ligand 1 (PD-L1) and PD-L2 and exert an anti-tumoral response. Considering the rich lipid sources of breast TME and the dependence on FA of tumor cells, lipid-associated macrophages may belong to the tissue-resident macrophage population that is reprogrammed by tumor cells [ 101 , 102 ]. On the contrary, another study showed that epidermal fatty acid-binding protein (E-FABP) is highly expressed in macrophages, particularly in a specific subset, promoting their antitumor activity.…”
Section: Plasticity Of Lipid Metabolismmentioning
confidence: 99%